Ciência da Computação - Correia, Ronaldo Celso Messias; Calsavara, Alcides; Serra, Ana Paula; Zampirolli, Francisco de Assis; Jonathan, Miguel (Computação Brasil, 2018)
Este artigo resume a história e as características dos cursos de Ciência da Computação no Brasil.